Errors in Writing Descriptive Text Made by the 8th GradeStudents of SMP Muhammadiyah 1 Kartasura in2015/2016 Academic Year - Setiani, Yuli, Prof. Endang Fauziati, M.Hum, Qanitah Masykuroh, S.S., M.Hum (2016)
This research aims at identifying writing descriptive text made by the 8th grade students of SMP Muhammadiyah 1 Kartasura in 2015/2016 academic year, especially: 1) to identify the types of morphological errors; 2) to identify the types of syntactical errors; 3) to identify the types of discourse errors; 4) to know the frequency of each type of errors; 5) to identify the dominant error made by students; and 6) to identify the source of errors. This research belongs to descriptive qualitative type. In collecting the data, the writer uses elicitation method. There were four steps to collect the data, namely: 1) the researcher entered the class, then asked the students about the descriptive text and ordered the students to make descriptive text, 2) the researcher collected of data in the form of erroneous sentences and paragraphs in writing descriptive text, 3) the researcher read and marked the types of error in the student's worked, 4) the researcher wrote the erroneous sentences and classified all types of error. The collected data are analyzed by using Dulay, Burt and Krashen's classification of errors theory, Bungin's the frequency of type of error theory and Brown's source of errors theory. The results of the research show that eighth grade students of SMP Muhammadiyah 1 Kartasura make 510 errors in their compositions. There are three classifications of error based on linguistic category and surface strategy taxonomy. First, lexical error consists of 74 errors or 14, 50% of errors. Second, syntactical errors consist of 386 errors or 75, 68% of errors. Third, discourse errors consist of 50 errors or 9, 80%. The dominated error is lexical errors in the form of which wrong spelling consists of 69 errors or 13, 52% of errors. In addition, the sources error of this errors are interlingual transfer (literal translation) and intralingual transfer which covers: ignorance of the rule restriction in rule of spelling, rule of verb, rule of possessive adjective and over-generalization in double marking in predicate.